How to develop SETS-based colloidal system teaching materials? - S Marfu’ah; S Anwar (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to develop SETS-based colloidal system teaching materials through 4S TMD method to develop students’ creativity. Research method in this study was Richey’s and Klein’s development research consisting of design, development, and evaluation. This study was conducted until the step of design and development. The procedure used in the development step was the 4S TMD method at the selection and structuring steps. The selection step consisted of curriculum analysis, indicators development, international textbooks analysis, and identification of values or aspects of SETS integrated into the teaching materials of the colloidal system. The structuring step had been developed concept maps, macro-structures, and multiple representations. The results of the selection and structuring steps had been reviewed and validated by expert lecturers in chemistry education. The results showed that the teaching materials developed were in accordance with the curriculum, scientifically correct, there were skills developed, and the SETS aspects was in accordance with the phenomenon presented.